Az állatcsont, mint információhordozó leletanyag - Csippán, Péter (Dissertationes Archaeologicae, 2013)
The aim of this paper is to rethink a special type of finds: animal bones. This kind of finds have more information than a simple biofact. And this is the first question: Is there a real category? What categories are useable for these things? The author of this paper tries to organize every type of data that are encoded in the animal bones and what is gathered during the manual identification. Using Clarke's entities of archaeological science (attribute, artefact, type, assemblage, culture, culture-group, technocomplex) we find that the animal bones are perfectly fitting in the set of things that we call: archaeological finds. For the application of these entities we have to rethink all of them for the needs of the interpretation of animal bones. Their explanation has three different facets: the taphonomical, the zoological and the cultural approaches. For understanding all encoded information we have to walk all the three ways to receive a complex and multilevel interpretation of these special types of the archaeological finds.